La grande théorie des crétins: Големата теорија за кретените - Grelet, Gilles; Jovanovski, Zoran (Identities: Journal for Politics, Gender and Culture, 2004)
Author(s): Gilles Grelet | Жил Греле Title (French): La grande théorie des crétins Title (Macedonian): Големата теорија за кретените Translated by (French to Macedonian): Zoran Jovanovski | Зоран Јовановски Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 269-275 Page Count: 7 Citation (French): Gilles Grelet, “La grande théorie des crétins,” Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004): 269-275. Citation (Macedonian): Жил Греле, „Големата теорија за кретените“, превод од француски Зоран Јовановски, Идентитети: списание за политика, род и култура, т. 3, бр. 2 (зима 2004): 269-275.